Strategy to Improve Service Continuity Performance Through Organizational Resilience and Business Continuity Management - Ganea Wijaya, Banu Surya; Madiawati, Putu Nina; Pradana, Mahir (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This research analyzes strategies for enhancing Service Continuity through the integration of Organizational Resilience (OR) and Business Continuity Management (BCM), with Digital Technology as a moderating variable. The study focuses on PT. ABC, a heavy equipment rental company operating in a critical sector that faces operational challenges arising from supply chain disruptions, manual systems, and limited digital coordination. These circumstances necessitate the implementation of an organizational resilience strategy capable of ensuring sustainable service continuity. A quantitative approach was adopted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The OR construct is modeled as a second-order formative construct comprising four dimensions: Anticipation, Readiness to Respond, Synchronization, and Proactive Learning. Data were collected through questionnaires distributed among respondents directly involved in the company’s risk management and operational activities. The analysis is further supported by Importance–Performance Map Analysis (IPMA) to identify strategic priorities for improving service performance. The results reveal that OR significantly influences BCM, and that BCM has both direct and indirect (mediating) effects on Service Continuity. Moreover, Digital Technology strengthens the relationship between BCM and Service Continuity, demonstrating that the integration of cloud-based systems, real-time monitoring, and digital access enhances organizational responsiveness to disruptions. Among the OR dimensions, Readiness to Respond and Proactive Learning emerge as key factors in service performance improvement. In conclusion, the integration of Organizational Resilience and Business Continuity Management, supported by the adoption of digital technology, substantially enhances resilience and service sustainability within critical operational sectors.